2022
DOI: 10.3390/gels8060353
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Polymer and Polymer Gel Treatments for Natural Gas-Related Conformance Control

Abstract: Conformance problems often exist in natural gas-related activities, resulting in excessive water production from natural gas production wells and/or excessive natural gas production from oil production wells. Several mechanical and chemical solutions were reported in the literature to mitigate the conformance problems. Among the chemical solutions, two classes of materials, namely polymer gels and water-soluble polymers, have been mostly reported. These systems have been mainly reviewed in several studies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 117 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…The effectiveness of gas blocking of cross-linked polymers or gels have been confirmed in many works, which present experimental and practical applications. , Gels in oilfield conditions have shown the ability to create a strong, long-term gas barrier. During the coreflooding experiments, it was observed that the gel is pumped into the core model with high resistance . This greatly affects the phase permeability of the oil, which in turn increases the risk of complete blocking of the formation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effectiveness of gas blocking of cross-linked polymers or gels have been confirmed in many works, which present experimental and practical applications. , Gels in oilfield conditions have shown the ability to create a strong, long-term gas barrier. During the coreflooding experiments, it was observed that the gel is pumped into the core model with high resistance . This greatly affects the phase permeability of the oil, which in turn increases the risk of complete blocking of the formation.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution, it was proposed to use a slug of a highly concentrated foam-forming surfactant solution before injection of the next foam slugs. Coreflooding tests on the core were also carried out for cross-linked agents . One of the early laboratory tests and field applications of gel in gas-shutoff technology was performed for the Prudhoe Bay field conditions .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most widely used group includes injection of polymers and cross-linkers. These are partially hydrolyzed polyacrylamides (HPAA) [ 28 , 29 ] cross-linked by polyvalent anions that change valence under reservoir conditions, or organic cross-linkers having a low kinetic constant [ 24 ]. For some cases, biopolymers [ 30 ] or other types of polymers are recommended.…”
Section: Methodsmentioning
confidence: 99%